2020
DOI: 10.18332/tid/117959
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of current tobacco smoking by adolescents in Nigeria: Interaction between school location and socioeconomic status

Abstract: INTRODUCTION Tobacco smoking is the largest preventable cause of global mortality, with its prevalence increasing in Sub-Saharan Africa, particularly among adolescents. We sought to determine the factors associated with tobacco smoking among Nigerian school adolescents and investigate the interaction between school location and socioeconomic status (SES). METHODS Using a cross-sectional study design, 4332 eighth to tenth grade students in rural and urban secondary schools in Enugu State, Nigeria, were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…For example, in addition to men, the study's target population included a subgroup of women who, on average, have lower income levels than men. According to the GAM, exposure to secondhand smoke at home had a strong relationship with smoking intensity (OR = 1.364), which is consistent with the results of the study by Itanyi et al (33). Therefore, due to the impact of environmental factors on people's tendency to smoke, interventions should be taken to reduce smoking in social environments, including the workplace, and also the necessary training should be provided to smoking parents.…”
Section: Discussionsupporting
confidence: 87%
“…For example, in addition to men, the study's target population included a subgroup of women who, on average, have lower income levels than men. According to the GAM, exposure to secondhand smoke at home had a strong relationship with smoking intensity (OR = 1.364), which is consistent with the results of the study by Itanyi et al (33). Therefore, due to the impact of environmental factors on people's tendency to smoke, interventions should be taken to reduce smoking in social environments, including the workplace, and also the necessary training should be provided to smoking parents.…”
Section: Discussionsupporting
confidence: 87%
“…This could be because most of our participants came from lower socioeconomic families, and as the study settings were around rural areas, most families were farmers and fishermen. Previous studies had shown that social disparities in parental smoking and young children’s exposure to SHS at home were correlated [ 2 , 5 ]. Another possible reason might be because parental smoking was measured differently.…”
Section: Discussionmentioning
confidence: 99%
“…More than six million of these deaths are the result of tobacco use, and nearly one million are nonsmokers who are exposed to secondhand smoke (SHS) [ 1 ]. Exposure of adolescents to SHS or tobacco advertisements and having smoking parents were positively associated with current tobacco smoking [ 2 ]. The nicotine contained in tobacco is highly addictive and a major risk factor for cardiovascular and respiratory diseases, as well as many different types of cancer caused by vascular disruption, inflammation, and endothelial dysfunction [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, an earlier report by the Global Youth Tobacco Survey of Nigeria established that one-in-five in school adolescents aged 13-15 years had ever attempted tobacco smoking, and about one-in-ten are currently smoking (Aniwada et al, 2018;Ekanem et al, 2010). More recently, the African Tobacco Control Alliance (2020) lamented the increased risk of tobacco smoking among school-going adolescents in Nigeria, which includes cancers of almost all organs of the body, central nervous system, heart and respiratory system (Itanyi et al, 2020). Itanyi et al (2020) attributed the high prevalence of tobacco consumption among adolescents in Nigeria to relaxed regulations on the control of the tobacco products by the Nigerian government.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the African Tobacco Control Alliance (2020) lamented the increased risk of tobacco smoking among school-going adolescents in Nigeria, which includes cancers of almost all organs of the body, central nervous system, heart and respiratory system (Itanyi et al, 2020). Itanyi et al (2020) attributed the high prevalence of tobacco consumption among adolescents in Nigeria to relaxed regulations on the control of the tobacco products by the Nigerian government. For instance, despite the Framework Convention on Tobacco Control Acts, Article 16 of which Nigeria is a signatory, tobacco is still being sold in single sticks which makes it affordable for the majority of adolescents.…”
Section: Introductionmentioning
confidence: 99%